The impact of clinical and psychological factors on asthma control: the experience of a single asthma center in Poland. (1st February 2022) - Przybyszowski, Marek; Pilinski, Rafal; Sliwka, Agnieszka; Polczyk, Romuald; Nowobilski, Roman; Sladek, Krzysztof; Bochenek, Grazyna
Abstract: Objective: The asthma control test (ACT) is commonly used to identify patients with uncontrolled asthma. The goal of this study was to determine whether clinical parameters such as asthma history and medications, exacerbation rate, comorbidities, lung function, and socioeconomic status are risk factors for uncontrolled asthma assessed with the ACT, and to evaluate the psychological status of controlled and uncontrolled asthmatics. Methods: Adult asthmatics ( n = 104) were recruited from a single asthma center, Poland. Asthma control was assessed with the ACT, using <20 as the cutoff point for uncontrolled asthma. Data on clinical factors were collected and spirometry was performed. Patients completed the Asthma Quality of Life Questionnaire, General Health Questionnaire, Acceptance of Illness Scale, Life Orientation Test-Revised, and Eysenck's Personality Inventory. Results: Asthma was uncontrolled in 42.3% of patients. Asthma exacerbations in the preceding 12 months and high inhaled corticosteroid (ICS) doses were identified as independent risk factors for uncontrolled asthma. Uncontrolled asthmatics had a significantly worse psychological status than controlled asthmatics. The groups did not differ in terms of personality traits, but in the controlled asthma group numerous significant correlations between psychological factors and personality traits were observed. In the uncontrolled asthma group, however, the occurrence of correlations between personality traits and other psychological variables was rarer. Conclusions: The study identified independent risk factors for uncontrolled asthma, namely, exacerbations in the recent 12 months and treatment with high-dose ICS. Uncontrolled asthmatics have a significantly worse psychological status than controlled asthmatics, irrespective of personality traits.